2014
DOI: 10.1111/ddi.12214
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a novel predator reveals extreme but highly variable mortality for an endangered migratory bird

Abstract: Aim Introduced predators are a global driver of species decline, but their impact on highly mobile species is poorly understood. We report the severe impact of a previously undocumented introduced predator on the endangered, migratory swift parrot (Lathamus discolor). Sugar gliders (Petaurus breviceps), a supposedly benign introduced species, were detected acting as a major opportunistic predator of cavity-nesting birds. We assessed the intensity and geographical extent of sugar glider predation and investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
111
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(123 citation statements)
references
References 37 publications
3
111
0
Order By: Relevance
“…In another study, number of fledglings produced by the Eclectus Parrot (Eclectus roratus) was significantly related to the depth and dryness of the nest cavity (Heinsohn 2008). Other studies have determined that factors such as forest canopy cover or proximity to waterways significantly influence nest success and productivity as these features may facilitate predator access to nests or be associated with anthropogenic activities (Bonebrake and Beissinger 2010;Britt et al 2014;Stojanovic et al 2014). In their study on 27 cavity-nesting bird species, including two small-bodied parrot species and three larger parrot species, Cockle et al (2015) observed that the nest success of the smaller cavity-nesting species was predicted by cavity height and entrance diameter, while tree condition was an important variable for nest success of larger species.…”
Section: Could Nest Site Selection By Psittaciformes Be Adaptive?mentioning
confidence: 99%
“…In another study, number of fledglings produced by the Eclectus Parrot (Eclectus roratus) was significantly related to the depth and dryness of the nest cavity (Heinsohn 2008). Other studies have determined that factors such as forest canopy cover or proximity to waterways significantly influence nest success and productivity as these features may facilitate predator access to nests or be associated with anthropogenic activities (Bonebrake and Beissinger 2010;Britt et al 2014;Stojanovic et al 2014). In their study on 27 cavity-nesting bird species, including two small-bodied parrot species and three larger parrot species, Cockle et al (2015) observed that the nest success of the smaller cavity-nesting species was predicted by cavity height and entrance diameter, while tree condition was an important variable for nest success of larger species.…”
Section: Could Nest Site Selection By Psittaciformes Be Adaptive?mentioning
confidence: 99%
“…In species where vocalizations are sexually dimorphic, such as the Ma'oma'o, using recordings and automatic techniques to recognize vocalizations may be useful for the future assessment of sex ratios. Employing such a method may be particularly useful for monitoring species where higher population declines are occurring in a single sex, such as Kaka (Greene andFraser 1998, Wilson et al 1998), Seychelles Magpie Robin (Copsychus sechellarum; Gerlach and Le Maitre 2001) and Swift Parrot (Stojanovic et al 2014). Understanding sex ratio differences may also be important in aiding conservation of the Ma'oma'o.…”
Section: Discussionmentioning
confidence: 99%
“…However, as it can be used on DNA from a molted feather, it is not always necessary to capture the bird. Techniques that overcome these restrictions are needed for robust management and conservation, particularly for declining species [e.g., Kaka (Nestor meridionalis; Wilson et al 1998); and Swift Parrot (Lathamus discolor; Stojanovic et al 2014)]. A quick, simple, field-based test of sex is particularly vital where a greater decline in one sex is suspected or knowledge of the sex ratio present in a population is needed for wildlife management (Martin 1996, Winkler and Preleuthner 2001, Wolfe et al 2010.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10). For example, Stojanovic et al (2014) clearly demonstrate the extreme cumulative impact on the Swift Parrot from forest management practices that reduce the amount of mature habitat available.…”
Section: Forestrymentioning
confidence: 99%